Avaliação de uma capacitação de psicólogos clínicos para identificação, intervenção e encaminhamento em caso de suspeita de abuso sexual infantil - Seras, Maria Josefa Rafart de (2012)
The capacitation of professionals for being able to work with child sexual abuse is still evaluated by scientific literature in a shy way, regardless of the good training of professionals who initially get in touch with abuse situations has to be a priority for handling those issues in an appropriate way. In the present work, A Capacitation of Clinic Psychologists for Identification, Intervention and Directioning in Case of Suspicion of Child Sexual Abuse was analysed in a quantitative way. It was a four-meetings process, with specific objectives: First Meeting – Introducing the participants in the sexual abuse theme, presenting scientific papers and the most common expressions used in sexual abuse studies, for identifying child sexual abuse. Second meeting – Awakening the self perception about the clinical practices of the participants, presenting their case studies, pointing eventual failures in their formation and performance in cases of child sexual abuse, and identifying the consequences of child sexual abuse. Third Meeting – Contexturing the signs of abuse in family and scholar life of the abused person, identifying the abuser´s carachteristics, and strategies used by him for carrying out and perpetuate the abuse, and identifying myths and trues about child sexual abuse. Fourth Meeting – Informing the participants about their legal possibilities in acting in case of suspect of child sexual abuse, and how to perform in case of suspition of child sexual abuse. The good commitment of the participants along the meetings, also creating a group for future studies about child sexual abuse, beyond the formation of a group for further studies about child sexual abuse, also designating future lectures to be carried on at schools, insinuate that the course was effective for the participant psychologists to be stimulated of turning into multipliers and continuing the studies about the theme.